Blueprint for health security in Nigeria by 2050: infectious diseases perspective (2019)
Background: Infectious Diseases remain a leading cause of morbidity and mortality in Nigeria. Notably, natural and socio-cultural differences across Nigeria account for significant differences in types of infectious diseases that occur in different parts of the country. The communicable nature of infectious diseases either from person to person or via vectors has made it difficult to eradicate or even stem the tide of these diseases. HIV/AIDS, tuberculosis and malaria in particular are well established and enduring contributors to the infectious disease burden in Nigeria and this is very likely to continue to be the case in the foreseeable future. Method: Literature from PubMed and Google was extracted using the keywords; Health Security, Year 2050 and Infectious Diseases Results: In more recent times in Nigeria, the problem of emerging and re-emerging infections, often of epidemic importance as well as antimicrobial resistance also add to the infectious disease burden and compete for the already inadequate resources available to battle infectious disease. Many infectious diseases can be prevented by simple, effective and relatively low-cost interventions. Such interventions need to be emphasized to maximize cost-effectiveness of any resources expended. Nigeria’s young, trainable, potential healthcare workforce and existing infrastructure such as the primary healthcare system, disease surveillance systems and widespread mobile phone use need to be strengthened arid leveraged for a good approach to infectious disease control. Conclusion: As Nigeria’s population is set to double by 2050, health security from an infectious disease standpoint will require policy change to support continuous training and re-training all cadres of healthcare workers to respond specifically to the problems that are fed back from the population while being fully aware of predictable (corruption, inadequate financing) and unpredictable (disease outbreaks, climate change, microbial mutation) factors that can serve as a hindrance.